Aetna, The SEC and Tax Benefits of Loss Carryforwards - Elliott, John A.; Swieringa, Robert J. (The Accounting Review, 1985)
[This article discusses several issues underlying a dispute between Aetna and the SEC about accounting for the tax benefits of loss carryforwards. We discuss current accounting requirements for these benefits, Aetna's accounting for its tax benefits, and the reaction of security markets to its dispute with the SEC. We believe that accounting for these tax benefits should be changed to reflect changes in the tax laws, current definitions of assets, and criteria for accounting recognition.]